2015
DOI: 10.1165/rcmb.2014-0082oc
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Hemolysin A Disrupts Cell–Matrix Adhesions in Human Airway Epithelial Cells

Abstract: Treatment of primary or immortalized human airway epithelial cells (16HBE14o-, S9) or alveolar cancer cells (A549) with recombinant hemolysin A (rHla), a major virulence-associated factor of Staphylococcus aureus, induces alterations in cell shape and formation of paracellular gaps in the cell layer. Semiquantitative Western blotting using extracts of freshly isolated airway tissue (nasal epithelium) or 16HBE14o- model cells revealed that phosphorylation levels of focal adhesion kinase (Fak) and paxillin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 49 publications
5
53
0
1
Order By: Relevance
“…2I). These findings demonstrated that, at a minimum, the basal plasma membranes of some NHBE cells were forming focal complexes with extracellular matrix or membrane substance (Berrier and Yamada, 2007;Hermann et al 2014).…”
Section: Discussionmentioning
confidence: 86%
“…2I). These findings demonstrated that, at a minimum, the basal plasma membranes of some NHBE cells were forming focal complexes with extracellular matrix or membrane substance (Berrier and Yamada, 2007;Hermann et al 2014).…”
Section: Discussionmentioning
confidence: 86%
“…Treatment of eukaryotic cells with Hla elicits various cell physiological effects ranging from apoptotic or necrotic cell death (16) or survival signaling (24,43) to changes in cell-cell or cell-matrix adhesion and actin cytoskeleton reorganization (19,60). Studies using cultured airway epithelial cells revealed that they respond to Hla treatment with ADAM10-mediated cleavage of cadherin (25).…”
mentioning
confidence: 99%
“…Studies using cultured airway epithelial cells revealed that they respond to Hla treatment with ADAM10-mediated cleavage of cadherin (25). We have recently shown that treatment of airway epithelial cells with recombinant Hla (rHla) results in accelerated turnover of focal adhesion complexes resulting in a net loss of peripheral focal contacts (19). Concomittant restructuring of the actin cytoskeleton results in the inability of cells to stabilize their cell shapes and in the appearance of paracellular gaps in the cell layer (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations